Peripheral Immune Dysfunction in ESCC with Lymph Node Metastasis: Implications for Preoperative Diagnosis and Prognosis - Yingcen Li; Bin Li; Helian Li; Jingyan Xu; Yali Luo; Jian Gao; Jingxuan Han; Xuling Han; Yiran Zhao; Alin Zhang; Feng Qian (Phenomics, 2026)

Correction: Deep Immunophenotyping of Human Whole Blood by Standardized Multi-parametric Flow Cytometry Analyses - Jian Gao; Yali Luo; Helian Li; Yiran Zhao; Jialin Zhao; Xuling Han; Jingxuan Han; Huiqin Lin; Feng Qian (Phenomics, 2024)

Self-standing CdS/TiO2 Janus nanofiberous membrane: COD removal, antibacterial activity and photocatalytic degradation of organic pollutants - Shiva Pandeya; Rui Ding; Yufei Ma; Xuling Han; Meixing Gui; Purnima Mulmi; Khim Prasad Panthi; Bhanu Bhakta Neupane; Hem Raj Pant; Ziliang Li; Mahesh Kumar Joshi (Journal of Environmental Chemical Engineering, 2024)

Analysis of the Immune Response by Standardized Whole-Blood Stimulation with Metabolism Modulation - Jialin Zhao; Xuling Han; Helian Li; Yali Luo; Yan Fang; Yun Wang; Jian Gao; Yiran Zhao; Jingxuan Han; Feng Qian (Phenomics, 2024)

Deep Immunophenotyping of Human Whole Blood by Standardized Multi-parametric Flow Cytometry Analyses - Jian Gao; Yali Luo; Helian Li; Yiran Zhao; Jialin Zhao; Xuling Han; Jingxuan Han; Huiqin Lin; Feng Qian (Phenomics, 2023)
Immunophenotyping is proving crucial to understanding the role of the immune system in health and disease. High-throughput flow cytometry has been used extensively to reveal changes in immune cell composition and function at the single-cell level. Here, we describe six optimized 11-color flow cytometry panels for deep immunophenotyping of human whole blood. A total of 51 surface antibodies, which are readily available and validated, were selected to identify the key immune cell populations and evaluate their functional state in a single assay. The gating strategies for effective flow cytometry data analysis are included in the protocol. To ensure data reproducibility, we provide detailed procedures in three parts, including (1) instrument characterization and detector gain optimization, (2) antibody titration and sample staining, and (3) data acquisition and quality checks. This standardized approach has been applied to a variety of donors for a better understanding of the complexity of the human immune system.